Historical Development of the Mongolian Ger (Architecture Image Studies, 2025)
The Mongolian ger, a portable felt dwelling, represents not only an architectural form but also a complex embodiment of the nomadic worldview, encompassing social organization, cultural values, economic practices, and aesthetic ideals (Bat-Yar, 2015). Its circular structure, symbolic elements, and practical design reflect a unique integration of functionality and spirituality, making the ger both a living space and a cultural text. This study traces the historical development of the Mongolian ger across different periods, drawing on archaeological evidence, historical chronicles, and ethnographic studies. Special attention is given to the 13th–14th centuries, when the ger served as a central dwelling in the Mongol Empire and demonstrated architectural interconnections with the Yuan dynasty in China. The research also analyzes the continuity of symbolic meanings embedded in structural elements such as the uni (roof poles), toono (crown), and lattice walls, which function not only as technical components but also as cultural metaphors of unity, order, and cosmology. Beyond historical inquiry, the study explores the potential for incorporating traditional ger features into contemporary interior design. By adapting structural patterns, spatial arrangements, and symbolic motifs, modern design practices may both preserve national identity and reinterpret cultural heritage for new generations. Such integration demonstrates that the ger is not a static relic of the past but a dynamic source of inspiration for sustainable and culturally grounded architectural solutions. The findings confirm that the Mongolian ger is more than a practical shelter; it is a multifaceted cultural heritage characterized by technical ingenuity, symbolic systems, and socio-ritual significance (Zhao, 2011; Khurelbaatar, 2018). Moreover, applying its principles to present-day design highlights the enduring relevance of nomadic traditions in shaping innovative, locally rooted approaches to modern living.